KERJASAMA SISTER CITY PEMERINTAH KOTA BANDUNG (INDONESIA) DAN PEMERINTAH KOTA PETALING JAYA (MALAYSIA) DALAM MENINGKATKAN INDUSTRI EKONOMI KREATIF BANDUNG TAHUN 2012-2016 - Mariane Olivia Delanova; Meizania Vania Utami Effendi; Yuswari Octonain Djemat (Universitas Jenderal Ahmad Yani, 2018)
In accordance with Law no.37 of 1999 on foreign relations and law no.32 of 2004 on regional government further strengthen the position of local government to conduct an external relationship in an effort to build its own region. The purpose of this study is to describe more deeply about the cooperation of sister city Bandung city government in improving the creative economy industry in Bandung City and Petaling Jaya City, Malaysia with the program